Problem-Based Learning e educação a distância: uma proposta para a educação estatística no ensino superior - Silva, Josney Freitas (2019)
This dissertation presents a qualitative research, outlined as a case study, whose objective was to present a proposal of Statistics Education in the modality of Distance Education, using the principles of the Problem-Based Learning method and the concepts of Statistical Education in Higher Education. For this purpose, an Extension Course on Statistical Topics was offered to students of the Administration and Accounting Courses of two Higher Education Institutions, one located in the interior of the State of São Paulo and the other in Minas Gerais. Five Extension students from the São Paulo institution participated in the Extension Course and a teacher from the Minas Gerais institution, who acted as tutor of the group. Students chose one representative to serve as leader and another student to be the group secretary. Two videoconferences via Google Hangouts were conducted to implement the steps of the Problem-Based Learning method. Students also used a WhatsApp group to communicate with each other and with the group tutor during the intervals between videoconferences. As a tool for the construction of the data, videotapes of videoconferences were recorded, the application of questionnaires to the students and the interview with the tutor. As a result, it was identified that the use of Information and Communication Technologies, such as Google Hangouts, Google Classroom and WhatsApp, helped the students, even geographically distant, to connect, have discussions about the resolution of a proposed problem, to promote group work and to learn concepts of Statistics.